Strategic Leadership in Developing a Culture of Literacy: A Case Study at SDIT Qurrota A’yun Ponorogo - Nazula, Desy; Anggraeni, Darsla Dyah Ayu; Nafiah, Ayu Zahroh (Yayasan Irwan Abdullah Cendekia, 2024)
The school principal not only leads but also determine the culture of literacy direction at SDIT Qurrota A’yun. The school principal is also actively involved in promoting the importance of culture of literacy today, particularly for students. This study aims to find out the school principal’s leadership strategy in developing a culture of literacy at SDIT Qurrota A’yun. This research uses a qualitative approach with a case study method. The data were obtained through observation, interviews, and documentation, and were analyzed using Miles, Huberman, and Saldana method. The results of the study show that school principal plays an important role in improving culture of literacy at the schools. The school principle is responsible for all activities in school and has a strategic responsibilty in improving students’ reading and writing skills. The school principal of SDIT Qurrota A’yun has a strong commitment in developing a culture of literacy, as evident by the launch of students authored book and increasing students’ interest in reading and writing. The implementation of this culture of literacy is supported by effective leadership and awareness of the importance of literacy in the schools. The results of this study can contribute to the development of leadership strategies in cultivating a culture of literacy in schools.